Antibiotic Resistance Awareness among Undergraduate Students in Quito, Ecuador - David Ortega-Paredes; César Marcelo Larrea-Álvarez; Lilibeth Torres-Elizalde; Sofia de Janon; Christian Vinueza-Burgos; Luis Hidalgo-Arellano; Miroslava Anna Šefcová; Gabriel Molina-Cuasapaz; Esteban Fernandez-Moreira; Marco Larrea-Álvarez (MDPI AG, 2022)
The inappropriate use of antibiotics leads to antibiotic resistance, which reduces their efficacy. The education of undergraduates is likely to influence their practices. Assessing awareness is critical in the general effort to confront the spread of antibiotic resistance. This cross-sectional investigation was carried out using the questionnaire "Antibiotic resistance: Multi-country public awareness" developed by the World Health Organization. Students from different backgrounds at the Central University participated in the study (n = 733). The survey comprised five sections: demographics, knowledge, usage, sources of information, and attitudes. The rate of correct answers was 64.88%; differences were detected between programs of study (p < 0.001); effect size analysis showed that these differences cannot be considered large. Individuals from applied sciences scored higher than their counterparts from social studies. Mostly, interviewees were knowledgeable about usage, but mistakenly associated antibiotics with conditions such as cold/flu or viral illnesses; also, they associated antibiotic resistance with the patient and not with bacteria. Despite these misconceptions, positive attitudes were registered overall, and students generally adhered to common practices. They cited doctors/nurses and teachers as sources of information. As a consequence, it is recommended to develop courses that address deficient knowledge regarding antibiotic resistance, especially for individuals affiliated to social disciplines.